The Effect of Education on Increasing Knowledge and Attitude of Pregnant Mothers Trimester III About Exclusive Breast Milk in the Clinic Sunartic Primary Year 2021 - Rosmani Sinaga (Institute of Computer Science (IOCS), 2021)
Breastfeeding for newborns is one of the efforts to prevent death and malnutrition in infants and toddlers. Data from the Health Profile of Medan City in 2016, the number of babies who received exclusive breastfeeding was 1,589 from 5,135 babies recorded, in a percentage of 30.9%. The purpose of this study was to study the effect of counseling on increasing knowledge and attitudes of pregnant women in the third trimester about exclusive breastfeeding before and after being given counseling at the Sunartik Pratama Clinic in 2021. This research is quantitative with research design using experimental method with pre-experimental using one group pre-post test method. The sampling technique used the total population with a sample of 31 respondents. The time of the study was carried out in March-July 2021. Data analysis used univariate and bivariate analysis using the Wilcoxon test. Based on the results of the study, there were differences in the average value of knowledge of third trimester pregnant women about exclusive breastfeeding before and after counseling, namely the Wilcoxon test results obtained the Asymp value. Sig. (2-tailed) is 0.000. And there is a difference in the average value of the attitude of pregnant women in the third trimester about exclusive breastfeeding before and after counseling, namely the Wilcoxon test results obtained by the Asymp value. Sig. (2-tailed) is 0.003. There is an effect of increasing knowledge and attitudes of pregnant women in the third trimester about exclusive breastfeeding before and after being given counseling. It is hoped that health workers can run government programs and provide counseling, information and counseling about the benefits of exclusive breastfeeding to increase knowledge of pregnant women who will breastfeed and give exclusive breastfeeding to babies 0-6 months.